2020
DOI: 10.1001/jamanetworkopen.2020.26010
|View full text |Cite
|
Sign up to set email alerts
|

Association of State Stay-at-Home Orders and State-Level African American Population With COVID-19 Case Rates

Abstract: Key Points Question Are stay-at-home orders and state-level proportion of African American residents associated with coronavirus 2019 (COVID-19) infection rates? Findings In this cross-sectional study including 3023 daily state-level observations from March to May 2020, results from multivariate regression models indicated that stay-at-home orders were associated with reductions in cumulative COVID-19 case rates. States with larger African American populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…During June 1–September 30, counties in states without statewide closures or closure periods <59 days, or without statewide mask mandates at reopening, were more likely to experience sharp increases in COVID-19 incidence during the summer after adjustment for county population size. These findings are consistent with other studies that demonstrated the effect of community mitigation policies in reducing spread of COVID-19 [7] , [ 9 , 10 , 19 , 20 ]. Longer statewide closures and mask mandates might have had an impact on slowing the acceleration of COVID-19 incidence, with more pronounced associations in less urban counties.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…During June 1–September 30, counties in states without statewide closures or closure periods <59 days, or without statewide mask mandates at reopening, were more likely to experience sharp increases in COVID-19 incidence during the summer after adjustment for county population size. These findings are consistent with other studies that demonstrated the effect of community mitigation policies in reducing spread of COVID-19 [7] , [ 9 , 10 , 19 , 20 ]. Longer statewide closures and mask mandates might have had an impact on slowing the acceleration of COVID-19 incidence, with more pronounced associations in less urban counties.…”
Section: Discussionsupporting
confidence: 93%
“…Although the evidence of the positive impact of the community mitigation policies on the burden of COVID-19 is increasing, the evidence of the impact of these policies at a local level is limited. Several individual state- or county-level investigations have shown the efficacy of mask mandates in reducing COVID-19 transmission 7 , 8 , 9 , 10 , but no studies have systematically examined the effect of community mitigation measures on rapid increases in COVID-19 incidence across the entire nation. Further, associations have not been examined by urbanicity, which may be of strong interest given the differences in COVID-19 incidence over time by urbanicity [11] .…”
Section: Introductionmentioning
confidence: 99%
“…This includes effective actions such as university-wide screening, contact tracing, enforcing wearing masks indoors and strict social distancing, flexible making-up classes policies, etc. 11 Taiwan reported low rates of infection in their communities using such policies, however, this was in the context of societal-wide adoption of strict infection control practices. 12…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] The details of these social distancing restrictions, and their implementation or enforcement, vary over states and over time as the pandemic progresses; for example, many states partially reopened non-essential businesses in early summer but closed these businesses again due to surges of COVID-19 in the second wave of the pandemic. Although recent studies examined variations of these state social distancing measures and demonstrated their effectiveness on reducing COVID-19 related morbidity and mortality, [22][23][24][25][26] the state COVID-19 policies examined in these studies were generally limited to the early stage of the pandemic (i.e. March to May of 2020).…”
Section: Discussionmentioning
confidence: 99%
“…22 Recent studies suggested the effectiveness of these state social distancing measures on curbing COVID-19 cases, hospitalizations, and associated deaths among the general population. [22][23][24][25][26] However, there is lack of evidence as to how these state orders may have affected the most vulnerable groups, such as LTC patients, or what potential negative health consequences they may have had, such as excess mortality due to reasons other than COVID -19 infection.…”
Section: Introductionmentioning
confidence: 99%